Pathological mechanisms of connexin26-related hearing loss: Potassium recycling, ATP-calcium signaling, or energy supply? - Chen, Penghui; Wu, Wenjin; Zhang, Jifang; Chen, Junmin; Li, Yue; Sun, Lianhua; Hou, Shule; Yang, Jun (Frontiers in Molecular Neuroscience, 2022)
Hereditary deafness is one of the most common human birth defects. GJB2 gene mutation is the most genetic etiology. Gap junction protein 26 (connexin26, Cx26) encoded by the GJB2 gene, which is responsible for intercellular substance transfer and signal communication, plays a critical role in hearing acquisition and maintenance. The auditory character of different Connexin26 transgenic mice models can be classified into two types: profound congenital deafness and late-onset progressive hearing loss. Recent studies demonstrated that there are pathological changes including endocochlear potential reduction, active cochlear amplification impairment, cochlear developmental disorders, and so on, in connexin26 deficiency mice. Here, this review summarizes three main hypotheses to explain pathological mechanisms of connexin26-related hearing loss: potassium recycling disruption, adenosine-triphosphate-calcium signaling propagation disruption, and energy supply dysfunction. Elucidating pathological mechanisms underlying connexin26-related hearing loss can help develop new protective and therapeutic strategies for this common deafness. It is worthy of further study on the detailed cellular and molecular upstream mechanisms to modify connexin (channel) function.